Advances in solar tower technology. Issue 1 (4th August 2016) - Alexopoulos, Spiros; Hoffschmidt, Bernhard
Abstract : This article begins with a short introduction and continues with a presentation of solar tower power plants around the world. The focus is set on the developments of the last five years and in the near future of the most important components of a central receiver system (CRS). For each of the components, a description of each technology, its applicability, and the advantages and disadvantages is presented. The chapter also includes a state of the art review for almost each system and points out the Research and Development (R&D) needs. A further issue is the choice of the heat‐transfer fluid (HTF) as well as the improvement of new solar tower power plant cycle systems. The paper introduces recent R&D activities, with the majority occurring in Europe and the United States, as has been presented in international journals and conferences by scientific personnel. It also reflects opinions of experts who specialized in the planning and erection of solar power plants and carrying out CRS research projects. The future effort of R&D in these fields should improve efficiencies, increase durability and reliability, and reduce investment and Operation & Maintenance (O&M) costs. Nowadays, and in this decade, the most advances in CRS occur in the United States, in Europe, and in China. Furthermore, a great interest, especially for add‐ons to existing research platforms as well as the construction of new ones, can be observed for the last years for countries in the Middle East & North Africa region, such as Morocco as well as India, Australia, and South Africa. WIREs Energy Environ 2017, 6:e217. doi: 10.1002/wene.217 This article is categorized under: Concentrating Solar Power > Science and Materials Concentrating Solar Power > Systems and Infrastructure Concentrating Solar Power > Climate and Environment Abstract : DLR's Solar Power Tower in Juelich, Germany, Source: DLR